Low dielectric loss calcium-boron-silicate glass / alumina composite and method of making
Patent Information
- Application Number
- CN202611421345.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0010]本发明旨在针对现有CBS/Al2O3复合LTCC材料中CBS玻璃组成对复合材料性能的影响规律不明确、现有技术缺乏不依赖外加剂即可实现超低介电损耗的无铅CBS/Al2O3复合材料的技术难题,提供一种组成简单、不依赖外加剂、在低温下烧结并具有超低介电损耗的钙硼硅玻璃/氧化铝复合材料及其制备方法
[0057]1.实现了超低介电损耗:本发明通过系统研究CaO含量(5-15wt%)对CBS玻璃性能的影响规律,发现当CaO含量为10wt%、B2O3/SiO2=0.45时,CBS玻璃/Al2O3复合材料在875℃下烧结可获得最低的介电损耗。优化配方(CBS玻璃组成为10%CaO+28%B2O3+62%SiO2,即B2O3/SiO2=0.45,CBS:Al2O3=45:55)在875℃下烧结,介电常数低至5.46@1MHz,介电损耗低至1.7×10-4@1MHz,10GHz下介电常数为5.92,介电损耗为1.46×10-3,实现了超低介电损耗,且低损耗效果在不依赖任何外加剂的条件下取得,与现有技术需添加K2O、LiF或Nb2O5等外加剂方能达到相近损耗水平的方案相比,具有意料不到的协同增益与更优的批一致性及电极共烧兼容性。
Smart Images

Figure CN122977822A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic materials technology, specifically to a calcium borosilicate glass / alumina composite material for low-temperature co-fired ceramics (LTCC) and its preparation method, and particularly to an LTCC substrate material with low dielectric constant and low dielectric loss. Background Technology
[0002] With the rapid development of 5G mobile communication technology, electronic devices are constantly evolving towards miniaturization, portability, high frequency, and high reliability. This has created an urgent need for miniaturized, integrated, and high-frequency electronic components. Low-temperature co-fired ceramic (LTCC) technology is gaining increasing attention due to its characteristics of low dielectric loss, high operating frequency (up to 40GHz), small size, and high stability. Furthermore, it allows for the formation of three-dimensional structures by embedding capacitors and inductors within the circuit, significantly reducing circuit size. The basic requirements for LTCC materials in high-frequency applications are a low dielectric constant, a high quality factor, and a resonant frequency temperature coefficient as close to zero as possible.
[0003] Glass / ceramic composite systems are often the preferred choice for LTCC materials due to their advantages, such as performance optimization through adjusting the glass content, good dielectric properties, and high mechanical properties. The sintering mechanism of this system is liquid-phase sintering: during the heating process, the low-softening-point glass melts to generate a liquid phase, which wets the ceramic particles. The flow of this liquid phase fills the pores between the particles, thereby achieving densification at a low temperature of 850-950℃.
[0004] Alumina (Al2O3) ceramics are characterized by their low dielectric constant. ≈10), low dielectric loss ( <10 -5 It possesses excellent properties such as high flexural strength (greater than 300 MPa) and high thermal conductivity (greater than 18 W / m·K), and is widely used as a ceramic filler in LTCC composites. However, its intrinsic sintering temperature is as high as 1600℃ or more, requiring the addition of low softening point glass to lower the sintering temperature to meet the requirements of the LTCC process.
[0005] Calcium borosilicate (CaO-B2O3-SiO2, CBS) glass-ceramics are considered one of the most promising LTCC glass phase systems due to their lower sintering temperature, thermal expansion coefficient matching that of silicon, and low dielectric constant and dielectric loss at high frequencies. During sintering, CBS glass-ceramics typically precipitate crystalline phases such as CaSiO3, SiO2, and CaB2O4. Among these, the CaSiO3 phase exhibits a moderate dielectric constant in the microwave frequency band. ≈5) with lower dielectric loss ( ≈1×10 -4 ~4×10 -4 ).
[0006] However, existing CBS / Al2O3 composite material systems still have the following shortcomings:
[0007] Existing research lacks a systematic study on the effects of varying CaO content in CBS glass on its melting temperature, fluidity, wettability, dielectric properties, and densification behavior after compositing with Al2O3. The influence of CBS glass composition on the properties of the composite material remains unclear. In particular, how to achieve ultra-low dielectric loss (at 1MHz) while ensuring low-temperature sintering (850-950℃) without adding any additives (such as K2O, LiF, Nb2O5, etc.) is a key challenge. <2×10 -4 There is a lack of clearly disclosed solutions in the existing technology. Although some existing technologies have achieved low dielectric loss by adding a variety of additives, the introduction of additives may bring potential problems such as batch consistency and compatibility with co-firing with electrodes, and increase the complexity of the material system and the preparation cost.
[0008] The closest existing technology is the CBS / Al2O3 system disclosed in reference [D1]: JH Jean et al., “Low-temperature firing of aCaO-B2O3-SiO2glass / alumina composite”, Journal of the American Ceramic Society, 1999, 82(4): 901–907 (DOI: 10.1111 / j.1151-2916.1999.tb01853.x), which has a dielectric constant of about 5.9–6.4 and a dielectric loss of about (3–5) × 10 at 1 MHz after sintering at 850–900 °C. -4 Furthermore, no compensation was made for the temperature coefficient τf of the resonant frequency (τf is a large negative value, approximately −100 to −150 ppm / °C); Reference [D2]: KK Moon et al., “Low-temperature firing and dielectric properties of CaO-B2O3-SiO2glass / Al2O3composites”, Journal of Electroceramics, 2003, 11: 109–115, which introduced alkali metal oxide additives such as Li2O to reduce the sintering temperature, but its 1MHz loss was still higher than 4×10 -4Furthermore, τf is difficult to adjust to near zero, and additives introduce batch consistency and electrode co-firing compatibility issues. None of the aforementioned existing technologies disclose achieving ultra-low dielectric loss (1.7 × 10⁻⁶) simultaneously through the synergistic control of CaO content and the B₂O₃ / SiO₂ ratio without additives. -4 The near-zero τf (level) and the near-zero τf are precisely the differentiating technical features of this invention compared with the prior art (for detailed difference data, please refer to the comparison under the same conditions in Table 6 of the specific implementation method).
[0009] Unlike existing technologies that use additives such as K2O, LiF, and Nb2O5 to lower sintering temperature or control dielectric properties, this invention is the first to discover that the CaO content in the CBS / Al2O3 system has a double-edged sword effect on crystallization and densification—too low CaO leads to high glass phase viscosity and poor wettability to Al2O3, resulting in under-sintering; too high CaO induces excessive crystallization of anorthite (CaAl2Si2O8), interrupts densification, and causes over-sintering expansion. It is precisely through the synergistic control of the additive-free CaO content and the B2O3 / SiO2 ratio that a 1.7 × 10⁻⁶ ohmmeter at 1 MHz is achieved at 875℃. -4 The ultra-low dielectric loss is a key feature. The optimal range (CaO≈10%, B2O3 / SiO2≈0.45) is not a conventional choice readily apparent in the art and is therefore non-obvious. Consequently, there is a pressing need in the art for a lead-free CBS / Al2O3 composite LTCC material with a simple composition, no dependence on additives, capable of low-temperature sintering, and exhibiting ultra-low dielectric loss. Summary of the Invention
[0010] This invention aims to address the technical challenges of unclear influence of CBS glass composition on composite material performance in existing CBS / Al2O3 composite LTCC materials and the lack of lead-free CBS / Al2O3 composite materials that can achieve ultra-low dielectric loss without the need for additives. The invention provides a calcium borosilicate glass / alumina composite material with simple composition, no need for additives, sintering at low temperature and exhibiting ultra-low dielectric loss, as well as its preparation method.
[0011] To achieve the above objectives, the present invention provides a low-dielectric-low-loss calcium borosilicate glass / alumina composite material, comprising the following components by mass percentage:
[0012] Calcium borosilicate glass: 40%–48%;
[0013] Alumina: 52%–60%;
[0014] The sum of the mass percentages of calcium borosilicate glass and alumina is 100%.
[0015] The oxide composition of calcium borosilicate glass, by mass percentage, includes the following components:
[0016] CaO: 5%–15%;
[0017] B2O3: 25%–28%;
[0018] SiO2: 57%~62%;
[0019] The mass ratio of B2O3 to SiO2 is 0.40 to 0.50; wherein CaO, B2O3, and SiO2 are the main oxide components of the calcium borosilicate glass, and the remainder is the raw material or unavoidable impurities in the preparation process.
[0020] In this invention, CaO is used as a network modifier, and B... 3+ and Si 4+ As a network form, the choice of CaO content is crucial: If the CaO content is too low (<5%), the glass phase viscosity is too high, resulting in poor wettability of Al2O3 and insufficient sintering densification; if the CaO content is too high (>15%), the glass phase viscosity is too low, resulting in excessive reactivity, which promotes excessive precipitation of the anorthite (CaAl2Si2O8) crystal phase. Excessive crystallization will rapidly consume the glass phase, interrupting the continuous densification process and potentially inducing abnormal crystal growth and expansion of closed pores, ultimately leading to decreased density and deterioration of dielectric properties. In this invention, the mass ratio of B2O3 to SiO2 is 0.40–0.50, a range derived from the oxide composition range of 25–28% B2O3 and 57–62% SiO2. The B2O3 / SiO2 ratio also affects the glass network structure and crystallization behavior. When the ratio is too low (<0.40), the glass network is too dense and the melting temperature increases. When the ratio is too high (greater than 0.50), the chemical stability of the glass decreases.
[0021] Preferably, the oxide composition of the calcium borosilicate glass is 10% CaO, 28% B2O3, and 62% SiO2, with a mass ratio of B2O3 to SiO2 of 0.45.
[0022] Preferably, the mass ratio of calcium borosilicate glass to alumina is 45:55.
[0023] Preferably, the alumina is granular α-Al2O3 with an average particle size of 1–3 μm.
[0024] Preferably, the powder D50 of the calcium borosilicate glass is 1 to 5 μm; more preferably, the powder D50 of the calcium borosilicate glass is 1 to 2 μm.
[0025] Preferably, the composite material does not contain K2O, LiF, and Nb2O5.
[0026] The present invention also provides an LTCC substrate material, which is obtained by sintering the above-mentioned calcium borosilicate glass / alumina composite material at 850℃~900℃. The substrate material has a dielectric loss of ≤5×10 at 1MHz. -4 Bulk density ≥ 2.70 g / cm³ 3 .
[0027] This invention also provides a method for preparing a low-dielectric-low-loss calcium borosilicate glass / alumina composite material, comprising the following steps:
[0028] S1: Raw material weighing and mixing
[0029] Based on an oxide composition of 5%–15% CaO, 25%–28% B2O3, and 57%–62% SiO2, with a B2O3 / SiO2 ratio of 0.40–0.50, raw materials of CaCO3, H3BO3, and SiO2 were weighed out separately, mixed evenly with anhydrous ethanol as the ball milling medium, and then dried. CaCO3 provides CaO through high-temperature decomposition (CaCO3→CaO+CO2↑), and H3BO3 provides B2O3 through dehydration (2H3BO3→B2O3+3H2O↑).
[0030] S2: High-temperature melting
[0031] The dried mixed powder is melted at 1400℃~1500℃ for 2~4 hours to obtain a uniform glass melt.
[0032] S3: Water quenching cooling
[0033] The molten glass is poured into water for cooling and quenching to obtain a glass block.
[0034] S4: Crushing and Ball Milling
[0035] The glass block was crushed and ball-milled to obtain calcium borosilicate glass powder with a D50 of 1–5 μm.
[0036] S5: Preparation of Composite Powders
[0037] The calcium borosilicate glass powder obtained from S4 was mixed with Al2O3 powder at a mass ratio of 40-48:52-60, ball-milled, dried, and sieved to obtain a composite powder.
[0038] S6: Granulation and Molding
[0039] A binder is added to the composite powder for granulation, followed by pressing to form a green body.
[0040] S7: Debinding and Sintering
[0041] The green body is debinded and sintered. The temperature is raised to 500℃ at a rate of 1-2℃ / min and held for debinding. Then the temperature is raised to 825℃-925℃ at a rate of 3-6℃ / min and held for 1-3 hours for sintering. After cooling to room temperature, a low dielectric and low loss calcium borosilicate glass / alumina composite material is obtained.
[0042] Preferably, in S4, the D50 of the glass powder is 1-2 μm; in S5, the mass ratio of calcium borosilicate glass powder to Al2O3 powder is 45:55.
[0043] Preferably, in S2, the melting temperature is 1450℃ and the melting time is 3 hours; in S7, the sintering temperature is 875℃, the sintering holding time is 2 hours, and the glue removal holding time is 5 hours.
[0044] Technical Principles
[0045] The technical principle by which this invention achieves the above-mentioned beneficial effects is as follows:
[0046] (1) Control principle of CBS glass composition
[0047] In the CaO-B2O3-SiO2 ternary system, Ca 2+ As a network modifier, it disrupts the glass network structure, lowering the glass's melting temperature and high-temperature viscosity. When the CaO content is 10 wt%, the glass phase exhibits suitable viscosity and fluidity: it can fully melt at the sintering temperature to generate sufficient liquid phase to fill the gaps between Al2O3 particles, without causing excessive crystallization or overheating due to excessively low viscosity. Simultaneously, the B2O3 / SiO2 ratio of 0.45 ensures the stability of the glass network structure, avoiding the decrease in chemical stability caused by excessive B2O3 or the increase in melting temperature caused by excessive SiO2.
[0048] (2) Principle of densification by liquid phase sintering
[0049] At a sintering temperature of 825-925℃, CBS glass first melts to form a liquid phase. The liquid phase promotes densification through the following steps: ① Particle rearrangement: The liquid phase wets and lubricates Al2O3 particles, which rearrange under the action of surface tension to fill pores; ② Dissolution-precipitation: Al2O3 particles partially dissolve in the liquid phase and precipitate at the particle contact necks, promoting the growth and bonding of necks between particles; ③ Pore filling: The liquid phase fills the remaining open pores, ultimately obtaining a dense sintered body.
[0050] (3) Regulation principle of anorthite crystallization
[0051] During sintering, CaO in CBS glass reacts with Al2O3 and SiO2 to form anorthite (CaAl2Si2O8). The formation behavior of anorthite under different CaO contents has drastically different effects on the sintering process and final properties of the material:
[0052] When the CaO content is too low (e.g., 5 wt%), the glass phase has high viscosity and poor wettability to Al2O3 ceramic particles, making it difficult for anorthite to form. This results in insufficient sintering driving force and low material density (bulk density of only 2.72 g / cm³). 3 The dielectric loss is relatively high (4.3×10). -4 @1MHz).
[0053] When the CaO content is 10wt%, the glass phase viscosity is moderate and the reactivity is suitable, allowing anorthite to form appropriately at a temperature of approximately 875℃, effectively promoting the densification of the material (bulk density 2.85 g / cm³). 3 Meanwhile, the glass phase structure is relatively stable, and the dielectric loss reaches its lowest value (1.7×10). -4 @1MHz).
[0054] When the CaO content is too high (≥15wt%), the excessive low-viscosity glass phase leads to premature and excessive precipitation of anorthite, which rapidly consumes the glass phase, interrupts the continuous densification process, and induces abnormal crystal growth and expansion of closed pores. Ultimately, this results in macroscopic expansion of the green body and a decrease in density (bulk density drops to 2.60-2.45 g / cm³). 3 And the dielectric properties deteriorated across the board (dielectric loss increased to 3.2 × 10⁻⁶). -4 ~1.6×10 -3 @1MHz).
[0055] Therefore, there is a key "degree" in the formation of anorthite: the optimal balance point is when the CaO content is 10wt%. Moderate precipitation is beneficial to densification and performance optimization, while too high or too low CaO content will lead to performance degradation.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] 1. Achieved ultra-low dielectric loss: This invention, through systematic research on the influence of CaO content (5-15 wt%) on the performance of CBS glass, found that when the CaO content is 10 wt% and B2O3 / SiO2 = 0.45, the lowest dielectric loss can be obtained when the CBS glass / Al2O3 composite material is sintered at 875℃. An optimized formula (CBS glass composition of 10% CaO + 28% B2O3 + 62% SiO2, i.e., B2O3 / SiO2 = 0.45, CBS:Al2O3 = 45:55) sintered at 875℃ resulted in a dielectric constant as low as 5.46@1MHz and a dielectric loss as low as 1.7 × 10⁻⁶. -4 At 1MHz and 10GHz, the dielectric constant is 5.92 and the dielectric loss is 1.46 × 10⁻⁶. -3 It achieves ultra-low dielectric loss, and the low loss effect is achieved without relying on any additives. Compared with the existing technology that requires the addition of additives such as K2O, LiF or Nb2O5 to achieve a similar loss level, it has unexpected synergistic gains and better batch consistency and electrode co-firing compatibility.
[0058] 2. Simple composition and high reliability without the need for additives: Unlike existing technologies that achieve low dielectric loss by adding additives such as K2O, LiF, and Nb2O5, this invention achieves ultra-low dielectric loss solely by controlling the composition of the CBS glass itself (CaO content and B2O3 / SiO2 ratio), without adding any additives. This not only simplifies the material composition and preparation process, reducing costs, but also avoids problems such as batch consistency, long-term reliability, and electrode co-firing compatibility that may arise from additives.
[0059] 3. Excellent long-term reliability: After 2042 hours of aging test at 100V and 125℃, the dielectric loss of the material of this invention only decreased from 1.7×10⁻⁶. -4 The change is 2.0 × 10 -4 At 1MHz, the rate of change is approximately 18%; the dielectric constant remains constant at 5.46, with a rate of change almost zero. These performance changes meet the practical requirements of a dielectric loss change rate ≤20% and a dielectric constant change rate ≤5%, indicating stable material properties.
[0060] 4. Low raw material cost and simple process: The raw materials used in this invention are only CaCO3, H3BO3, SiO2, and Al2O3, all of which are common industrial raw materials with low cost. The preparation process is simply glass melting → water quenching → milling → ball milling → composite → molding → sintering, which is a simple process route suitable for industrial mass production. Attached Figure Description
[0061] Figure 1 This is a flowchart illustrating the preparation process of the CBS glass / Al2O3 composite LTCC sample of the present invention.
[0062] Figure 2 This is the glass composition design diagram based on the Ca-B-Si ternary phase diagram of the present invention;
[0063] Figure 3 This is a graph showing the glass melting process of the present invention;
[0064] Figure 4 This is a process curve diagram of the glue removal and sintering of the present invention;
[0065] Figure 5 This is a particle size distribution diagram of the glass powder of the present invention;
[0066] Figure 6 This is an experimental diagram of the melt wetting of CBS glass with different CaO contents on an alumina plate at 1000℃ according to the present invention.
[0067] Figure 7 This is a viscosity calculation graph of glasses with different CaO contents at 875℃ based on FactSage thermodynamic software, according to the present invention.
[0068] Figure 8 This is a phase analysis diagram of CBS glass powder with different CaO contents according to the present invention;
[0069] Figure 9 This is a phase analysis diagram of the CBS glass / Al2O3 composite LTCC sample of the present invention;
[0070] Figure 10 This is a statistical diagram of the CaAl2Si2O8 crystal phase precipitation in the CBS glass / Al2O3 composite LTCC sample of the present invention;
[0071] Figure 11 The image shows the cross-sectional morphology of the composite material of 10wt% CaO CBS glass and Al2O3 in different proportions after sintering at 875℃ according to the present invention.
[0072] Figure 12 This is a diagram showing the sintering porosity of different CaO contents at 875℃ according to the present invention.
[0073] Figure 13 The thermogravimetric analysis chart is shown for the composite of 10wt% CaO CBS glass and Al2O3 according to the present invention. Detailed Implementation
[0074] The present invention will be further described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. All raw materials used in the embodiments are commercially available industrial-grade raw materials, wherein the purity of CaCO3, H3BO3, and SiO2 is ≥99%, and the Al2O3 powder is α-Al2O3 with an average particle size of 1-3 μm. In the present invention, CBS glass is calcium borosilicate glass. No additives such as K2O, LiF, or Nb2O5 are added in any of the embodiments.
[0075] Example 1 (Basic Formula)
[0076] I. Preparation of CBS Glass
[0077] The ingredients were prepared according to the oxide composition of 10g CaO, 28g B2O3, and 62g SiO2 (i.e., B2O3 / SiO2 = 0.45). The conversion to raw materials is as follows:
[0078] CaCO3: 10×(100.09 / 56.08)=17.85g;
[0079] H3BO3: 28×(123.66 / 69.62)=49.73g;
[0080] SiO2: 62.00g.
[0081] The above raw materials were placed in a ball mill, with anhydrous ethanol as the ball milling medium. The mass ratio of large, medium and small zirconia ball milling beads (diameters of 15 mm, 10 mm and 5 mm respectively) was 1:3:3. The ball milling was carried out at a speed of 280 r / min for 6 hours to ensure that the powder was fully mixed and then dried.
[0082] The dried mixed powder was placed in an alumina crucible and dehydrated with boric acid at 300℃ for 2 hours, followed by melting at 1450℃ for 3 hours to obtain a homogeneous glass melt. The specific glass melting procedure is as follows:
[0083] Room temperature → 300℃ (heating up for 200 min) → 300℃ (holding for 120 min) → 1450℃ (heating up for 115 min) → 1450℃ (holding for 180 min) → Cooling with the furnace.
[0084] Molten glass is rapidly poured into deionized water for cooling and quenching, resulting in glass blocks of uneven size.
[0085] The glass block was first mechanically crushed, then further ground in a disc mill until D50 ≤ 150 μm. Subsequently, it was ball-milled for 15 hours with anhydrous ethanol as the medium until the glass was crushed to D50 of 1–2 μm. After drying, CBS glass powder was obtained. No additives such as K2O, LiF, or Nb2O5 were added in this embodiment.
[0086] II. Preparation of Composite Materials
[0087] The CBS glass powder and Al2O3 powder were mixed at a mass ratio of 45:55 (i.e., 45g CBS glass and 55g Al2O3). The mixture was placed in a ball mill and milled for 6 hours at 280 rpm using anhydrous ethanol as the milling medium to ensure thorough mixing and further refinement of the glass powder and Al2O3. The milled slurry was dried at 100℃ for 12 hours, thoroughly ground, and then passed through a 60-mesh sieve to obtain the composite powder.
[0088] Add a 5 wt% polyvinyl alcohol (PVA) solution (10 wt% of the powder mass) dropwise to the composite powder, grind and granulate thoroughly, and pass through a 40-mesh sieve. Weigh an appropriate amount of powder evenly into a mold, press it under a pressure of 6 MPa and hold for 20 seconds to form cylindrical (Φ12mm×1mm) and strip (40mm×5mm×5mm) green bodies respectively.
[0089] The pressed green body is placed in a high-temperature sintering furnace for debinding and sintering:
[0090] Debinding stage: The temperature is increased from room temperature to 500℃ at a rate of 1.6℃ / min and held for 5 hours;
[0091] Sintering stage: The temperature is increased from 500℃ to 875℃ at a heating rate of 5℃ / min, and held for 2 hours;
[0092] Cooling stage: The furnace is cooled to room temperature to obtain a dense LTCC composite material.
[0093] III. Performance Testing
[0094] Dielectric property testing: Dielectric constant and dielectric loss were measured at 1MHz using an Agilent 4294A impedance analyzer. The test sample was a silver-plated disc measuring Φ12mm × 1~2mm. Dielectric constant... Calculated using the following formula:
[0095]
[0096] In the formula: The capacitance value (F) of the sample was measured at 1MHz. The thickness (m) of the silver coating on the ceramic sample; The vacuum permittivity is 8.85 × 10⁻⁶. -12 F / m; The area (m²) of the ceramic tile coated with silver.
[0097] The dielectric constant and dielectric loss at 10 GHz were tested using an E5080b vector network analyzer. The test sample was a strip with a cross-section of 2 mm × 2 mm and a length slightly greater than 30 mm.
[0098] Bulk density test: The bulk density of the sintered sample was determined using Archimedes' displacement method. The sintered disc-shaped sample was placed on a density meter to measure its mass (m3) in air. Then, the sample was immersed in deionized water, and its mass (m1) in the water was measured. The total mass (m2) of the sample being displaced into the deionized water was also measured. The bulk density of the sample was calculated using the following formula:
[0099]
[0100] In the formula: The bulk density of the sample (g / cm³) 3 ); The density of deionized water (g / cm³) 3 ).
[0101] Bending strength test: The three-point bending method is used. The height h and width b of the strip sample are measured with vernier calipers. The sample is placed horizontally on the support of the universal testing machine, and both ends are fixed with clamps. A force is slowly applied to the middle of the strip sample until it breaks. The computer automatically calculates the bending strength of the sample according to the following formula:
[0102]
[0103] In the formula: Flexural strength (MPa); Width (mm) of the bottom clamp of the universal testing machine; The maximum value of the fracture load (N); The width of the sample is (mm). The thickness of the sample is (mm). The experimental results are the average of 5 samples.
[0104] Performance test results:
[0105] Dielectric constant: 5.46 @ 1MHz;
[0106] Dielectric loss: 1.7 × 10 -4 @1MHz;
[0107] Dielectric constant: 5.92 @ 10 GHz;
[0108] Dielectric loss: 1.46 × 10 -3 @10GHz;
[0109] Bulk density: 2.85 g / cm³ 3 ;
[0110] Bending strength: 153±8MPa.
[0111] Example 2 (Comparative Experiment with Different CaO Contents)
[0112] With a fixed B2O3 / SiO2 ratio of 0.45, CBS glasses with CaO contents of 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, and 30wt% were prepared (corresponding to the same raw material conversion ratios and preparation methods as in Example 1). These glasses were then mixed with Al2O3 at a ratio of 45:55 and sintered at 875℃. The performance test results are shown in Table 1.
[0113] Table 1: Performance test results of samples with different CaO contents
[0114] 5wt% 5.4 <![CDATA[4.3×10 -4 ]]> 2.72 Partially dense 10wt% 5.5 <![CDATA[1.7×10 -4 ]]> 2.85 Good density 15wt% 6.3 <![CDATA[3.2×10 -4 ]]> 2.82 Good density 20wt% 7.0 <![CDATA[6.0×10 -4 ]]> 2.84 Mild overheating 25wt% 7.3 <![CDATA[8.0×10 -4 ]]> 2.60 Overheating expansion 30wt% 8.1 <![CDATA[1.6×10 -3 ]]> 2.45 Severe expansion
[0115] The results showed that the dielectric loss was lowest (1.7 × 10⁻⁶) when the CaO content was 10 wt%. -4 @1MHz), with the highest bulk density (2.85g / cm³). 3 When the CaO content is 5 wt%, densification is insufficient; when the CaO content increases to above 20 wt%, the dielectric loss increases significantly. It is worth noting that although the bulk density is slightly higher at 20 wt% CaO compared to 15 wt%, the dielectric loss has already increased from 3.2 × 10⁻⁶. -4 It increased dramatically to 6.0 × 10 -4 This indicates that the microstructure has begun to deteriorate. While overheating may initially be accompanied by a brief increase in density, dielectric properties deteriorate before density. Therefore, dielectric loss is a more sensitive performance evaluation indicator than bulk density. Excessive CaO content promotes excessive crystallization of anorthite (CaAl2Si2O8), leading to decreased density and deterioration of dielectric properties. Therefore, the preferred range for CaO is determined to be 5-15 wt%, with an optimal value of 10 wt%.
[0116] Figure 12 The porosity diagrams for the above samples with different CaO contents after sintering at 875℃ are shown, where (a) 5wt% CaO: porosity 7.65%; (b) 10wt% CaO: porosity 0.18%; (c) 15wt% CaO: porosity 0.02%; (d) 20wt% CaO: porosity 0.89%; (e) 25wt% CaO: porosity 8.85%; and (f) 30wt% CaO: porosity 3.25%. Figure 12As shown in Table 1, the trends of porosity and dielectric loss are well consistent: the porosity is lowest (0.18%–0.02%) and the dielectric loss is lowest when the CaO content is 10–15 wt%. When the CaO content is too low or too high, the porosity increases significantly (7.65%–8.85%), and the dielectric loss also increases accordingly, indicating that the degree of densification is one of the key factors affecting dielectric loss.
[0117] Example 3 (Comparative Experiment with Different Glass / Ceramic Ratios)
[0118] The CBS glass composition of Example 1 (10% CaO, B2O3 / SiO2=0.45) was used, and the mixtures were prepared at mass ratios of CBS:Al2O3 of 35:65, 40:60, 45:55, and 50:50, respectively, and sintered at 875°C (the preparation method was the same as in Example 1). The performance test results are shown in Table 2.
[0119] Table 2: Performance test results of samples with different CBS:Al2O3 ratios
[0120] 35:65 5.5 <![CDATA[4.1×10 -4 ]]> 2.49 Insufficient densification 40:60 5.8 <![CDATA[2.5×10 -4 ]]> 2.72 Partially dense 45:55 5.5 <![CDATA[1.7×10 -4 ]]> 2.85 Good density 50:50 6.3 <![CDATA[6.8×10 -4 ]]> 2.65 Slight swelling
[0121] The results showed that the optimal overall performance was achieved when the CBS:Al2O3 ratio was 45:55. When the glass phase ratio was too low (35:65), the amount of liquid phase was insufficient to fully fill the gaps between Al2O3 particles, resulting in inadequate densification. When the glass phase ratio was too high (≥50:50), the excessive low-viscosity glass phase led to premature and excessive precipitation of anorthite, rapidly consuming the glass phase, interrupting the densification process, and inducing the expansion of closed pores, causing macroscopic expansion and performance degradation of the green body. Therefore, the preferred range for CBS:Al2O3 was determined to be 40-45:55-60, with 45:55 being the optimal ratio.
[0122] Figure 11 The images show the sintered cross-sectional morphology of the samples with different ratios, where (a) CBS glass:Al2O3 = 35:65; (b) CBS glass:Al2O3 = 40:60; (c) CBS glass:Al2O3 = 45:55; and (d) CBS glass:Al2O3 = 50:50. (Combined with...) Figure 11 As shown in Table 2, when the CBS glass ratio is 45:55, the cross-sectional morphology is the most compact and the pores are the fewest. When the ratio is too low (35:65), a large number of residual pores can be seen in the cross-section, and the compaction is insufficient. When the ratio is too high (50:50), abnormal grain growth and closed-cell expansion are observed in the cross-section, which is consistent with the trend of dielectric property deterioration.
[0123] Example 4 (Comparative experiment at different sintering temperatures)
[0124] The formulation of Example 1 (CBS glass with 10% CaO, B2O3 / SiO2 = 0.45, CBS:Al2O3 = 45:55) was used, and sintered at different temperatures (the preparation method was the same as in Example 1). The performance test results are shown in Table 3.
[0125] Table 3: Performance test results of samples at different sintering temperatures
[0126] 825℃ 5.5 <![CDATA[8.2×10 -4 ]]> 2.58 Insufficient densification 850℃ 5.9 <![CDATA[1.9×10 -4 ]]> 2.72 Partially dense 875℃ 6.2 <![CDATA[1.7×10 -4 ]]> 2.85 Good density 900℃ 6.4 <![CDATA[3.2×10 -4 ]]> 2.79 Mild overheating 925℃ 7.1 <![CDATA[5.7×10 -4 ]]> 2.72 Overheating expansion
[0127] The results showed that 875℃ was the optimal sintering temperature, at which the dielectric loss was lowest and the bulk density was highest. At temperatures below 850℃, the glass phase lacked fluidity, resulting in incomplete densification; at temperatures above 900℃, overheating occurred, leading to deterioration of dielectric properties. Therefore, the preferred sintering temperature range was determined to be 850-900℃, with 875℃ being the optimal value.
[0128] Example 5 (Dielectric properties of a fixed formulation at different frequencies)
[0129] Using the optimized formulation of Example 1, the dielectric properties at different frequencies were tested, and the results are shown in Table 4.
[0130] Table 4: Dielectric properties at different frequencies
[0131] 1MHz 5.46 <![CDATA[1.7×10 -4 <!-- 8 -->]]> 10GHz 5.92 <![CDATA[1.46×10 -3 ]]>
[0132] The results show that the material of the present invention maintains low dielectric constant and low dielectric loss at both 1MHz and 10GHz frequencies, exhibits good frequency stability, and is suitable for high-frequency microwave applications.
[0133] Example 6 (Aging Life Test)
[0134] The sample prepared using the optimized formulation of Example 1 was subjected to an aging life test at 100V and 125℃ for 2042 hours. The test results are shown in Table 5.
[0135] Table 5: Aging Life Test Results
[0136] Dielectric constant @ 1MHz 5.46 5.46 0% Dielectric loss @ 1MHz <![CDATA[1.7×10 -4 ]]> <![CDATA[2.0×10 -4 ]]> +18%
[0137] The results show that after aging for 2042 hours at 100V and 125℃, the dielectric constant of the material of this invention remains unchanged, and the dielectric loss change rate is only 18%, which meets the practical application requirements of dielectric loss change rate ≤20% and dielectric constant change rate ≤5%, proving that the material has excellent long-term reliability.
[0138] Comparative Example 1 (CaO content exceeds the preferred range)
[0139] CBS glass with a CaO content of 25 wt% (B2O3 / SiO2 = 0.45) was mixed with Al2O3 at a ratio of 45:55 and sintered at 875 °C (preparation method is the same as in Example 1). The dielectric loss was 7.3 × 10⁻⁶. -4 @1MHz, bulk density is 2.62g / cm³ 3 It is significantly inferior to Example 1 (dielectric loss 1.7 × 10⁻⁶). -4 Bulk density 2.85 g / cm³ 3 This indicates that excessive CaO content leads to deterioration of dielectric properties.
[0140] Comparative Example 2 (glass ratio exceeds the preferred range)
[0141] The CBS glass composition of Example 1 (10% CaO, B2O3 / SiO2 = 0.45) was used, but the CBS:Al2O3 ratio was changed to 50:50, and sintering was performed at 875°C (the preparation method was the same as in Example 1). The sample showed significant expansion, with a bulk density of only 2.65 g / cm³. 3 The dielectric loss is as high as 6.8×10 -4 @1MHz cannot meet the requirements of LTCC applications. This indicates that an excessively high glass ratio leads to excessive crystallization and expansion. It should be noted that a 50:50 ratio is already at the boundary of the mass ratio range of calcium borosilicate glass to alumina in this invention (glass phase at the upper limit, Al2O3 at the lower limit). At this point, the amount of liquid phase reaches a critical excess state, resulting in excessive crystallization of anorthite, expansion of closed pores, and performance degradation. This also illustrates the necessity of preferably controlling the mass fraction of the glass phase at 40% to 48% and the alumina at 52% to 60% (optimal 45:55).
[0142] Comparative Example 3 (Under the same conditions with added LiF admixture)
[0143] Using the optimized formulation of Example 1 (CBS glass composition: CaO 10%, B2O3 28%, SiO2 62%, B2O3 / SiO2 = 0.45, CBS:Al2O3 = 45:55), only 2wt% LiF was added to the composite powder (the remaining raw materials and processes were the same as in Example 1), and sintering was performed at 875℃. The dielectric constant was measured to be 5.62@1MHz, and the dielectric loss was 4.6×10⁻⁶. -4 @1MHz, bulk density 2.79 g / cm³. Compared with Example 1, although LiF can lower the temperature of the sintering liquid phase, Li... + Introducing non-bridging oxygen into the glass network and increasing ion migration loss raises the dielectric loss at 1 MHz by approximately 2.7 times (4.6 × 10⁻⁶). -4 vs 1.7×10 -4Furthermore, LiF's high hygroscopicity poses risks to batch consistency and long-term reliability. This indicates that the additive LiF did not produce a synergistic gain superior to that of the present invention; instead, it degraded dielectric loss.
[0144] Comparative Example 4 (Under the same conditions with Nb2O5 admixture added)
[0145] Using the optimized formulation of Example 1, only 3 wt% Nb₂O₅ was added to the composite powder (the rest remained the same as in Example 1), and sintering was performed at 875 °C. The measured dielectric constant was 6.15 @ 1 MHz, and the dielectric loss was 3.8 × 10⁻⁶. -4 @1MHz, bulk density 2.85 g / cm³. Compared with Example 1, Nb₂O₅ increased εr to 6.15 and dielectric loss at 1MHz by approximately 2.2 times (3.8 × 10⁻⁶). -4 vs 1.7×10 -4 Furthermore, while Nb₂O₅, being a high-valence ion, allows for adjustable τf, it significantly increases raw material costs. This indicates that the additive Nb₂O₅ also failed to achieve a synergistic gain superior to that of the present invention.
[0146] Comparative Example 5 (Reproducing the closest prior art D1, without additives but deviating from the preferred CaO range under the same conditions)
[0147] The same process as in Example 1 was used with CBS:Al2O3 = 45:55, but the CBS glass oxide composition was CaO 15%, B2O3 28%, and SiO2 62% (B2O3 / SiO2 = 0.45, CaO is at the upper limit of the range defined in this invention), and sintering was performed at 875°C (the rest is the same as in Example 1). The dielectric constant was measured to be 6.30@1MHz, and the dielectric loss was 3.2×10⁻⁶. -4 @1MHz, bulk density 2.82 g / cm³. This result corresponds to the data in Table 1 for CaO=15wt%, and the dielectric loss increases by approximately 1.9 times (3.2 × 10⁻⁶) compared to Example 1 (CaO=10wt%). -4 vs 1.7×10 -4 This demonstrates that even without adding any additives, as long as the CBS glass composition deviates from the preferred range of this invention, the loss increases significantly—further confirming the 1.7 × 10⁻⁶ range of this invention. -4 The ultra-low loss stems from the unexpected synergistic gain of "no additives + synergistic control of CaO content and B2O3 / SiO2 ratio".
[0148] Table 6: Comparison with CBS system containing LiF and Nb2O5 admixtures under the same conditions (benchmark: CBS:Al2O3=45:55, 875℃ / 2h)
[0149] This invention (Example 1) none 875℃ 5.46 <![CDATA[1.7×10 -4 ]]> 2.85 Comparative Example 3 LiF 2wt% 875℃ 5.62 <![CDATA[4.6×10 -4 ]]> 2.79 Comparative Example 4 <![CDATA[Nb2O53wt%]]> 875℃ 6.15 <![CDATA[3.8×10 -4 ]]> 2.85 Comparative Example 5 (Reproduction of D1) None (CaO=15wt%) 875℃ 6.30 <![CDATA[3.2×10 -4 ]]> 2.82
[0150] As shown in Table 6, under the same CBS:Al2O3 ratio of 45:55 and sintering conditions of 875℃ / 2h, the addition of LiF or Nb2O5 not only failed to further reduce dielectric loss, but also increased the loss at 1MHz by 1.9 to 2.7 times (Comparative Example 3: 4.6 × 10⁻⁶). -4 Comparative Example 4: 3.8 × 10 -4 Furthermore, Nb₂O₅ increases εr to 6.15, and LiF introduces risks related to moisture absorption and batch consistency. Even in a scheme without additives but where the CBS composition deviates from the preferred range (Comparative Example 5, CaO = 15 wt%), losses increase to 3.2 × 10⁻⁶. -4 The above comparison under the same conditions shows that the present invention has a strength of 1.7 × 10⁻⁶. -4 The ultra-low dielectric loss at @1MHz does not come from the CBS / Al2O3 matrix itself, but from the synergistic gain resulting from the combined effect of "no additives + synergistic regulation of B2O3 / SiO2 ratio".
[0151] Summary of Examples and Comparative Examples
[0152] Based on the test results of Examples 1-6 and Comparative Examples 1-2, the preferred technical solution determined by this invention is as follows: the CBS glass oxide composition is CaO 10%, B2O3 28%, and SiO2 62% (B2O3 / SiO2=0.45), the mass ratio of CBS glass to Al2O3 is 45:55, the sintering temperature is 875℃, and the holding time is 2h. Under this preferred solution, the dielectric constant of the composite material is as low as 5.46 at 1MHz, and the dielectric loss is as low as 1.7×10⁻⁶. -4 Its bulk density reaches 2.85 g / cm³. 3 The bending strength reaches 153±8MPa, the dielectric constant at 10GHz is 5.92, and the dielectric loss is 1.46×10⁻⁶. -3 It exhibits stable performance and excellent overall performance after 2042 hours of aging.
[0153] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material, characterized in that, It contains the following components by weight percentage: Calcium borosilicate glass: 40%–48%; Alumina: 52%–60%; The sum of the mass percentages of the calcium borosilicate glass and the alumina is 100%. The oxide composition of the calcium borosilicate glass, by mass percentage, comprises the following components: CaO: 5%–15%; B2O3: 25%–28%; SiO2: 57%~62%; Furthermore, the mass ratio of B2O3 to SiO2 is 0.40–0.50; The CaO, B2O3, and SiO2 are the main oxide components of the calcium borosilicate glass, with the remainder being unavoidable impurities in the raw materials or preparation process.
2. The low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material according to claim 1, characterized in that: The oxide composition of the calcium borosilicate glass is 10% CaO, 28% B2O3, and 62% SiO2, with a mass ratio of B2O3 to SiO2 of 0.
45.
3. The low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material according to claim 2, characterized in that: The mass ratio of the calcium borosilicate glass to the alumina is 45:
55.
4. The low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material according to claim 1, characterized in that: The alumina is granular α-Al2O3 with an average particle size of 1–3 μm.
5. The low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material according to claim 1, characterized in that: The powder D50 of the calcium borosilicate glass is 1-5 μm.
6. The low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material according to claim 1, characterized in that: The composite material does not contain K2O, LiF, or Nb2O5.
7. An LTCC substrate material, characterized in that: The substrate material is obtained by sintering the low dielectric and low loss calcium borosilicate glass / alumina composite material according to any one of claims 2 to 6 at 850°C to 900°C, wherein the dielectric loss of the substrate material at 1MHz is ≤5×10⁻⁶. -4 Bulk density ≥ 2.70 g / cm³ 3 .
8. A method for preparing a low-dielectric-loss, low-loss calcium borosilicate glass / alumina composite material, characterized in that, Includes the following steps: S1: According to the composition of oxides with CaO 5%~15%, B2O3 25%~28%, SiO2 57%~62% and B2O3 / SiO2=0.40~0.50, weigh CaCO3, H3BO3 and SiO2 raw materials respectively, mix them evenly with anhydrous ethanol as the ball milling medium and then dry them. S2: Melt the dried mixed powder at 1400℃~1500℃ for 2~4 hours to obtain a uniform glass melt; S3: Pour the molten glass into water for cooling and quenching to obtain a glass block; S4: The glass block is crushed and ball-milled to obtain calcium borosilicate glass powder, wherein the D50 of the glass powder is 1-5 μm; S5: The calcium borosilicate glass powder obtained in S4 is mixed with Al2O3 powder at a mass ratio of 40-48:52-60, ball-milled, dried, and sieved to obtain composite powder; S6: Add a binder to the composite powder, granulate it, press it into shape, and obtain a green body; S7: The green body is debinded and sintered. The temperature is raised to 500°C at a rate of 1-2°C / min and held for debinding. Then the temperature is raised to 825°C-925°C at a rate of 3-6°C / min and held for 1-3 hours for sintering. The green body is then cooled to room temperature to obtain the low dielectric and low loss calcium borosilicate glass / alumina composite material.
9. The preparation method according to claim 8, characterized in that: In step S4, the D50 of the glass powder is 1-2 μm; in step S5, the mass ratio of the calcium borosilicate glass powder to the Al2O3 powder is 45:
55.
10. The preparation method according to claim 8, characterized in that: In S2, the melting temperature is 1450℃ and the melting time is 3 hours; in S7, the sintering temperature is 875℃, the sintering holding time is 2 hours, and the glue removal holding time is 5 hours.